2016
DOI: 10.1039/c5nr08248j
|View full text |Cite
|
Sign up to set email alerts
|

Defect segregation and optical emission in ZnO nano- and microwires

Abstract: The spatial distribution of defect related deep band emission has been studied in zinc oxide (ZnO) nano- and microwires using depth resolved cathodoluminescence spectroscopy (DRCLS) in a hyperspectral imaging (HSI) mode within a UHV scanning electron microscope (SEM). Three sets of wires were examined that had been grown by pulsed laser deposition or vapor transport methods and ranged in diameter from 200 nm-2.7 μm. This data was analyzed by developing a 3D DRCLS simulation and using it to estimate the segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…And the emission band obviously redshifted as Ga atoms substitute for Zn sites in ZnO crystalline host lattice, which suggests that the V O ‐related defect modes decrease due to Ga‐doped effects. For Sample‐4, the redshift of the visible emission bands can be obtained as well . As the Ga content increases, the incorporated Ga ions exert a stronger effect on the optical properties of ZnO:Ga MWs in combination with the surface defect modes changing from V O ‐related donor levels to complex V O –Ga Zn related impurity levels, and finally turning into Ga Zn related impurity bands.…”
Section: Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…And the emission band obviously redshifted as Ga atoms substitute for Zn sites in ZnO crystalline host lattice, which suggests that the V O ‐related defect modes decrease due to Ga‐doped effects. For Sample‐4, the redshift of the visible emission bands can be obtained as well . As the Ga content increases, the incorporated Ga ions exert a stronger effect on the optical properties of ZnO:Ga MWs in combination with the surface defect modes changing from V O ‐related donor levels to complex V O –Ga Zn related impurity levels, and finally turning into Ga Zn related impurity bands.…”
Section: Resultsmentioning
confidence: 77%
“…In addition, defect spectroscopy of single ZnO MWs has been indicated that there is a characteristic deep defect levels inside the gap at 0.88 eV from the top of the VB, and a defect level next to the bottom of the CB at 0.11 eV (Figure S5, Supporting Information). The presence of these defect levels attribute to Zn i +2 and V Zn −2 , respectively . Moreover, it has been verified that the oxygen vacancies are the dominant acceptor defects in as‐grown ZnO MWs.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations